Clinical Studies and Pre-clinical Animal Models on Facial Nerve Preservation, Reconstruction, and Regeneration Following Cerebellopontine Angle Tumor Surgery–A Systematic Review and Future Perspectives - Hostettler, Isabel C.; Jayashankar, Narayan; Bikis, Christos; Wanderer, Stefan; Nevzati, Edin; Karuppiah, Ravindran; Waran, Vicknes; Kalbermatten, Daniel; Mariani, Luigi; Marbacher, Serge; Guzman, Raphael; Madduri, Srinivas; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Background and purpose: Tumorous lesions developing in the cerebello-pontine angle (CPA) get into close contact with the 1st (cisternal) and 2nd (meatal) intra-arachnoidal portion of the facial nerve (FN). When surgical damage occurs, commonly known reconstruction strategies are often associated with a poor functional recovery. This article aims to provide a systematic overview for translational research by establishing the current evidence on available clinical studies and experimental models reporting on intracranial FN injury. Methods: A systematic literature search of several databases (PubMed, EMBASE, Medline) was performed prior to July 2020. Suitable articles were selected based on predefined eligibility criteria following the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines. Included clinical studies were reviewed and categorized according to the pathology and surgical resection strategy, and experimental studies according to the animal. For anatomical study purposes, perfusion-fixed adult New Zealand white rabbits were used for radiological high-resolution imaging and anatomical dissection of the CPA and periotic skull base. Results: 144 out of included 165 publications were clinical studies reporting on FN outcomes after CPA-tumor surgery in 19136 patients. During CPA-tumor surgery, the specific vulnerability of the intracranial FN to stretching and compression more likely leads to neurapraxia or axonotmesis than neurotmesis. Severe FN palsy was reported in 7% to 15 % after vestibular schwannoma surgery, and 6% following the resection of CPA-meningioma. Twenty-two papers reported on experimental studies, out of which only 6 specifically used intracranial FN injury in a rodent (n=4) or non-rodent model (n=2). Rats and rabbits offer a feasible model for manipulation of the FN in the CPA, the later was further confirmed in our study covering the radiological and anatomical analysis of perfusion fixed periotic bones. Conclusion: The particular anatomical and physiological features of the intracranial FN warrant a distinguishment of experimental models for intracranial FN injuries. New Zealand White rabbits might be a very cost-effective and valuable option to test new experimental approaches for intracranial FN regeneration. Flexible and bioactive biomaterials, commonly used in skull base surgery, endowed with trophic and topographical functions, should address the specific needs of intracranial FN injuries.